1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Rat cGMP‐Binding cGMP‐Specific Phosphodiesterase mRNA in Purkinje Cell Layers During Postnatal Neuronal Development

Abstract: The cDNA encoding rat cGMP-binding, cGMP-specific phosphodiesterase (cGB-PDE) was isolated from a rat lung cDNA library. Although the deduced amino acid sequence showed 93.4% similarity with that of bovine cGB-PDE, the N-terminal portion of rat cGB-PDE was extremely different from that of bovine. Northern blot analysis indicated that cGB-PDE transcripts in rats were expressed not only in aorta and lung, but also in several other tissues including cerebellum. In situ hybridization analysis demonstrated that cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
74
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 54 publications
7
74
1
Order By: Relevance
“…An increase in cGMP, via activation of parallel fibers and climbing fibers, evokes long-term depression in Purkinje cells. In situ hybridization demonstrated that the cerebellar expression of PDE5 transcripts is limited to Purkinje cells (Kotera et al 1997). Local administration of zaprinast, a PDE5 inhibitor, leads to an increase of cGMP release from cerebellar slices and promotes induction of cerebellar long-term depression in rat cerebellar slices when paired with parallel fiber stimulation (Hartell 1996).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An increase in cGMP, via activation of parallel fibers and climbing fibers, evokes long-term depression in Purkinje cells. In situ hybridization demonstrated that the cerebellar expression of PDE5 transcripts is limited to Purkinje cells (Kotera et al 1997). Local administration of zaprinast, a PDE5 inhibitor, leads to an increase of cGMP release from cerebellar slices and promotes induction of cerebellar long-term depression in rat cerebellar slices when paired with parallel fiber stimulation (Hartell 1996).…”
Section: Discussionmentioning
confidence: 99%
“…We have isolated human, canine, and rat PDE5 cDNAs from lung cDNA libraries and here described cDNAs encoding two variants of PDE5 (PDE5A1 and PDE5A2) in these species (Kotera et al 1997. Our studies revealed high levels of PDE5 transcripts in rat cerebellum and intestine in addition to tissues containing VSMCs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…8,9) PDE5 is abundantly expressed in some specific tissues, including the lung and pulmonary artery. [10][11][12] Therefore, the inhibition of PDE5 is considered to produce an increase in cGMP levels in the lung and pulmonary artery. It has been reported that PDE5 inhibitors such as zaprinast, E-4021 and sildenafil preferably dilate the pulmonary artery in vivo and in vitro experimental conditions.…”
mentioning
confidence: 99%